2008
DOI: 10.1111/j.1365-2109.2008.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on the survival, growth and challenge infection in Tilapia nilotica (Oreochromis niloticus)

Abstract: This study was conducted in order to evaluate the potential bene¢t of Bacillus pumilus and a commercial product ('Organic Green' TM ) as a probiotic in the culture of the tilapia nilotica. Two doses of B. pumilus (10 6 and 10 12 g À1 diet fed) and Organic Green TM (1 and 2 g kg À1 diet fed) were used as feed additives and administered for periods of 1 (groups 2, 3, 4 and 5 respectively) and 2 (groups 6, 7, 8 and 9 respectively) months; group 1 served as a control. Each group consisted of 4 equal replicates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
124
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 31 publications
9
124
2
2
Order By: Relevance
“…It has been clearly demonstrated that probiotic dietary supplements can lead to improvements in feeding efficiency and growth rates in aquatic animals (Aly et al 2008, Abelli et al 2009, Campa-Cordova et al 2009). Probiotics can generate enhanced levels of relevant digestive enzymes (like amylase, protease, and lipase) in animal intestines, which in turn would increase the digestibility of organic matter and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that probiotic dietary supplements can lead to improvements in feeding efficiency and growth rates in aquatic animals (Aly et al 2008, Abelli et al 2009, Campa-Cordova et al 2009). Probiotics can generate enhanced levels of relevant digestive enzymes (like amylase, protease, and lipase) in animal intestines, which in turn would increase the digestibility of organic matter and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The curves displayed that initially after challenge mortality was observed in all groups however thereafter probiotic treated groups showed high survival while number of fishes declined in groups fed on control diets without probiotic supplementation revealing the immunostimulating effects of dietary probiotic supplementation. Earlier studies showed that dietary supplementation of probiotic bacteria significantly increases the disease resistances in Oncorhynchus mykiss (Panigrahi et al, 2005), Catla catla (Bandyopadhyay and Das Mohapatra, 2009), Labeo rohita (Nayak et al, 2007;Kumar et al, 2008), Oreochromis niloticus (Aly et al, 2008). The ability of probiotic bacteria to out-compete other bacteria for nutrients and space as well excluding other bacteria through metabolite production might have resulted in higher survival of fish (Verschuere et al, 2000).…”
Section: Dietary Treatmentsmentioning
confidence: 99%
“…FAO (2002) stated that few efficacious drugs or antibiotics are available but with increasing problem of emerging drug-resistant pathogens and the resultant food and environmental contamination therefore, disease prevention appears to be a better approach rather than treatment dependence for controlling infectious diseases. Additionally, antibiotics also affect the beneficiary normal microflora of the host digestive tract (Aly et al, 2008). Such increased concern has given impetus for the employment of several alternative husbandry methods for combating or controlling diseases including use of some beneficial microorganisms as probiotic.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria could also have improved digestive activity via synthesis of vitamins and cofactors or via enzymatic improvement [4]. Among probiotics, Bacillus strains have become more and more popular and widely used in fish aquaculture [19,20,24]. In the use of live prey, Artemia nauplii are widely recognized as the best natural storable live feed available and are extensively used in marine finfish and crustacean hatcheries throughout the world because of their nutritional and operational advantages [25,26] and have been used as a vector for the carrying of different materials, including probiotics [27].…”
Section: Discussionmentioning
confidence: 99%